Flexible Li‐CO2 Batteries with Liquid‐Free Electrolyte. (13th April 2017) - Hu, Xiaofei; Li, Zifan; Chen, Jun
Abstract: Developing flexible Li‐CO2 batteries is a promising approach to reuse CO2 and simultaneously supply energy to wearable electronics. However, all reported Li‐CO2 batteries use liquid electrolyte and lack robust electrolyte/electrodes structure, not providing the safety and flexibility required. Herein we demonstrate flexible liquid‐free Li‐CO2 batteries based on poly(methacrylate)/poly(ethylene glycol)‐LiClO4 ‐3 wt %SiO2 composite polymer electrolyte (CPE) and multiwall carbon nanotubes (CNTs) cathodes. The CPE (7.14×10 −2  mS cm −1 ) incorporates with porous CNTs cathodes, displaying stable structure and small interface resistance. The batteries run for 100 cycles with controlled capacity of 1000 mAh g −1 . Moreover, pouch‐type flexible batteries exhibit large reversible capacity of 993.3 mAh, high energy density of 521 Wh kg −1, and long operation time of 220 h at different degrees of bending (0–360°) at 55 °C.